2004
DOI: 10.1182/blood-2003-03-0713
|View full text |Cite
|
Sign up to set email alerts
|

Induction of microparticle- and cell-associated intravascular tissue factor in human endotoxemia

Abstract: The precise role of intravascular tissue factor (TF) remains poorly defined, due to the limited availability of assays capable of measuring circulating TF procoagulant activity (PCA). As a model of inflammation-associated intravascular thrombin generation, we studied 18 volunteers receiving an infusion of endotoxin. A novel assay that measures microparticle (MP)-associated TF PCA from a number of cellular sources (but not platelets) demonstrated an 8-fold increase in activity at 3 to 4 hours after endotoxin ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
223
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 272 publications
(239 citation statements)
references
References 56 publications
14
223
1
1
Order By: Relevance
“…Volunteers receiving an infusion of endotoxin exhibited an early increase in tissue factor + -microparticles and to a lesser extent of EMP. 28 Beneficial effects of microparticles in patients with septic shock were more recently suggested by Soriano et al 29 In their study, lower levels of endothelial, platelet and leukocytederived microparticles were associated with higher mortality rates and organ dysfunction. In septic shock, vascular hyporeactivity together with tissue hypoperfusion and hypoxia account for severe hypotension enabling amplification of the shock.…”
Section: Protective Effects Of Microparticles On Vascular Hyporeactivitymentioning
confidence: 85%
“…Volunteers receiving an infusion of endotoxin exhibited an early increase in tissue factor + -microparticles and to a lesser extent of EMP. 28 Beneficial effects of microparticles in patients with septic shock were more recently suggested by Soriano et al 29 In their study, lower levels of endothelial, platelet and leukocytederived microparticles were associated with higher mortality rates and organ dysfunction. In septic shock, vascular hyporeactivity together with tissue hypoperfusion and hypoxia account for severe hypotension enabling amplification of the shock.…”
Section: Protective Effects Of Microparticles On Vascular Hyporeactivitymentioning
confidence: 85%
“…56,58 In addition, activated ECs release TF-containing MPs, which could potentially be transferred to platelets as well. 59,60 Recent studies confirmed the possibility for true de novo TF protein expression in platelets upon stimulation by using metabolic radiolabeling. 54 ADP, a potent inducer of platelet activation, enhanced platelet TF activity.…”
Section: Granulocytesmentioning
confidence: 90%
“…TF is expressed by subendothelial cells that are not normally exposed to the circulating blood, but disruption of vascular integrity exposes TF and initiates the coagulation cascade (35). Inflammatory mediators and LPS induce the expression of TF on endothelial and polymorphonuclear cells and platelets, thereby increasing blood thrombogenicity (36,37).…”
Section: Discussionmentioning
confidence: 99%